Bilateral blockade of MEK- and PI3K-mediated pathways downstream of mutant KRAS as a treatment approach for peritoneal mucinous malignancies. - Murali R Kuracha; Peter Thomas; Brian W Loggie; Venkatesh Govindarajan (PLoS ONE)
Mucinous colorectal adenocarcinomas (MCAs) are clinically and morphologically distinct from nonmucinous colorectal cancers (CRCs), show a distinct spectrum of genetic alterations (higher KRAS mutations, lower p53, high MUC2), exhibit more aggressive behavior (more prone to peritoneal dissemination and lymph node involvement) and are associated with poorer response to chemotherapy with limited treatment options. Here, we report the effectiveness of combinatorial targeting of two KRAS-mediated parallel pathways in reducing MUC2 production and mucinous tumor growth in vitro and in vivo. By knockdown of mutant KRAS we show that, mutant KRAS (a) is necessary for MUC2 production in vitro and (b) synergistically engages PI3K/AKT and MEK/ERK pathways to maintain MUC2 expression in MCA cells. These results define a novel and a previously undescribed role for oncogenic KRAS in mucinous cancers. MCA cells were sensitive to MEK inhibition suggesting cellular dependence ('addiction') of KRAS-mutant MCA cells on hyperactivation of the MEK-driven pathway. Interestingly, MCA cells, though initially sensitive, were later resistant to PI3K single agent inhibition. Our studies suggest that this resistance involves dynamic rewiring of signaling circuits mediated through relief of RTK inhibition and MEK-ERK rebound activation. This resistance however, could be overcome by co-targeting of PI3K and MEK. Our studies thus provide a rational basis for MEK- and PI3K-targeted combination therapy for not only KRAS mutant MCA but also for other related mucinous neoplasms that overproduce MUC2 and have a high rate of KRAS mutations such as pseudomyxoma peritonei.